IMPROVING E-COMMERCE APPLICATION THROUGH SENSE OF AGENCY OF A CALIBRATED INTERACTIVE VR APPLICATION (Journal of Information and Communication Technology, 2022)
Virtual Reality (VR) technologies create and control different virtual world instead of the actual environment, and this contributes to the feeling of control known as the sense of agency (SoA). The SoA exists from the contrast between the expected sensory consequence of one’s action from efference copy and the real sensory effects. However, the size representation of objects differs between the physical and virtual world due to certain technical limitations, such as the VR application’s virtual hand not reflecting the user’s actual hand size. A limitation that will incur low quality of perception and SoA for digital application. Here, we proposed a proof-of-concept of an interactive e-commerce application that incorporates VR capability and size calibration mechanism. The mechanism uses a calibration method based on the reciprocal scale factor from the virtual object to its real counterpart. The study of the SoA focusing on user perception and interaction was done. The proposed method was tested on twenty two participants − who are also online shopping users. Nearly half of the participants (45%) buy online products frequently, at least one transaction per day. The outcome indicates that our proposed method improves 47% of user perception and interaction compared to the conventional e-commerce application with its static texts and images. Our proposed method is rudimentary yet effective and can be easily implemented in any digital field.